IDNLearn.com offers a comprehensive solution for all your question and answer needs. Ask your questions and get detailed, reliable answers from our community of knowledgeable experts.
Sagot :
By def. of the derivative, we have for y = ln(x),
[tex]\displaystyle \frac{dy}{dx} = \lim_{h\to0} \frac{\ln(x+h)-\ln(x)}{h}[/tex]
[tex]\displaystyle \frac{dy}{dx} = \lim_{h\to0} \frac1h \ln\left(\frac{x+h}{x}\right)[/tex]
[tex]\displaystyle \frac{dy}{dx} = \lim_{h\to0} \ln\left(1+\frac hx\right)^{\frac1h}[/tex]
Substitute y = h/x, so that as h approaches 0, so does y. We then rewrite the limit as
[tex]\displaystyle \frac{dy}{dx} = \lim_{y\to0} \ln\left(1+y\right)^{\frac1{xy}}[/tex]
[tex]\displaystyle \frac{dy}{dx} = \frac1x \lim_{y\to0} \ln\left(1+y\right)^{\frac1y}[/tex]
Recall that the constant e is defined by the limit,
[tex]\displaystyle e = \lim_{y\to0} \left(1+y\right)^{\frac1y}[/tex]
Then in our limit, we end up with
[tex]\displaystyle \frac{dy}{dx} = \frac1x \ln(e) = \boxed{\frac1x}[/tex]
In Mathematica, use
D[Log[x], x]
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com has the solutions to your questions. Thanks for stopping by, and come back for more insightful information.